Analisis Strategi Efektif Pengelolaan Anggaran Guna Peningkatan Kualitas Operasional Pendidikan SMKN 1 Pinrang - Dwi Utami; Sri Utami (Academic Bright Collaboration, 2024)
In delivering quality education, effective budget management iscrucial for SMK Negeri 1 Pinrang. This article presents an in-depth analysis of budget management strategies that have proven successful in improving the operational quality of education at the school. Byutilizing School Operational Assistance (BOS) funds transparently and systematically, the school has been able to allocate financialresources appropriately to support every aspect of education, from purchasing teaching materials to improving facilities. Through a structured approach to planning, budgeting, and accountability, SMK Negeri 1 Pinrang serves as an inspiring example for other schools in optimizing the use of funds to enhance the quality of education.